Predator-prey Model with Different Growth Rates and Different Functional Responses: A Comparative Study with Additional Food - Sahoo, Banshidhar (International Journal of Applied Mathematical Research, 2012)
A predator-prey model with different types of growth rates and differentfunctional responses is proposed. The stable dynamics of the system for different growth rates have been shown. The results of the system with additional food to predator for different growth rates have been shown in this context. The coexistence of species in the system depends on the growth rates of the prey species. We have suggested that a real predator-prey model will be constructed with different growth rates and different functional responses.